Embolization of cranial dural arteriovenous fistulas in the liquid embolic era: A Sydney experience. (March 2018) - Johnson, Catherine S.; Chiu, Albert; Cheung, Andrew; Wenderoth, Jason
Highlights: We report on a Sydney, Australia cohort of cranial dural arteriovenous fistulas. Within our cohort the complete obliteration rate was 89.6%. The complication rate was 8.3%. Routine use of liquid embolic agents such as Onyx for the treatment of cranial dural arteriovenous fistulas is safe and effective. Abstract: Endovascular management of dural arteriovenous fistulas has become a mainstay of treatment. In particular, modern techniques have allowed greater fistula penetration and likelihood of complete obliteration. However, the efficacy of newer agents has not been quantified outside of predominantly small case reports and case series. Furthermore, the Australian experience with fistula embolization has yet to be reported in the literature. To this aim, we performed a retrospective review of our endovascular management of a large cohort of cranial dural arteriovenous fistulas in the liquid embolic era. This retrospective case series included ninety-six consecutive patients of any Cognard grade, treated between 2005 and 2016. Liquid embolic agents were used exclusively in eighty-three cases. The overall complete obliteration rate was 89.6% with a residual fistula rate of 2%, and complication rate of 8.3%. This Sydney, Australia cohort demonstrates excellent treatment effect and safety outcomes and thus supports the primary treatment of this condition by endovascular means.